Biopharmaceutical classification of desloratadine – not all drugs are classified the easy way - Berginc Katja; Sibinovska Nadica; Žakelj Simon; Trontelj Jurij; Legen Igor (Acta Pharmaceutica)
The biopharmaceutical classification of drugs was designed as a basis for bio-waivers – a mechanism with the double ethical benefit of delivering new drug formulations to the market with less human testing and lower cost. However, many drugs defy simple classification because in vitro permeability and stability assessment can be challenging as shown in this study for desloratadine. Literature shows that desloratadine is highly soluble, while data on luminal stability and permeability are circumstantial. Combined with borderline bioavailability and not really known fraction of absorbed dose, desloratadine was found to be a good example for showing the innovative in vitro approaches necessary to unambiguously classify desloratadine according to Biopharmaceutical Classification System (BCS) guideline. Presented study undoubtedly confirmed that desloratadine solubility is high and dissolution is very rapid for immediate release reference tablets. We have demonstrated deslorata-dine stability under legally required conditions and also in more physiologically relevant media. High in vitro desloratadine permeability was confirmed using Caco-2 and Parallel Artificial Membrane Permeability Assay (PAMPA). Well-established in vitro model with rat intestinal tissue could not be used due to reasons elaborated in this paper.